2014
DOI: 10.3171/2014.4.jns131212
|View full text |Cite
|
Sign up to set email alerts
|

Twist-drill craniostomy with hollow screws for evacuation of chronic subdural hematoma

Abstract: Object. The incidence of chronic subdural hematoma (CSDH) is expected to increase substantially over the next 25 years. Continuing refinement of techniques for surgical evacuation is essential for optimizing patient outcomes. A novel technique involving a hollow screw, which is threaded through a twist-drill hole in the cranium and then connected to a closed drainage system, has been increasing in popularity. The aim of this systematic review is to collate and analyze the published experience with this novel t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 18 publications
2
27
1
Order By: Relevance
“…This is reflected in the number of studies that reported this outcome (96; 94.1%) and the number of studies that set out to specifically examine factors that influenced recurrence (22; 21.6%). However, as we identified during our recent systematic review of minimally-invasive techniques for CSDH, 22 the heterogeneity in definitions and time-points of recurrence precludes amalgamation of data and undermines any attempt at meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected in the number of studies that reported this outcome (96; 94.1%) and the number of studies that set out to specifically examine factors that influenced recurrence (22; 21.6%). However, as we identified during our recent systematic review of minimally-invasive techniques for CSDH, 22 the heterogeneity in definitions and time-points of recurrence precludes amalgamation of data and undermines any attempt at meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Today, common treatment variants include a twist-drill craniostomy, burr-hole procedure with passive subdural drainage, subgaleal (or subperiosteal) active (suction) drainage, and continuous irrigation. 2,5,[7][8][9]21 There is no evidence supporting the superiority of one specific drainage technique, and adequately powered comparative studies evaluating the different drainage techniques after burrhole evacuation are lacking. 11,14 The aim of this population-based, retrospective, comparative cohort study was to compare recurrences after CSDH burr-hole surgery in regions served by neurosurgical centers using different postoperative drainage techniques.…”
mentioning
confidence: 99%
“…Class I evidence is necessary to optimize the surgical management of patients with CSDH. 7 Wang et al introduced a new modified TDC technique using a novel device, the YL-1 puncture needle, and evaluated its efficacy and advantages compared with BHC.…”
Section: Discussionmentioning
confidence: 99%